Flexible transgastric endoscopic liver cyst fenestration: A feasibility study in humans (with video). Issue 51 (December 2016) - Wang, Dong; Liu, Yaping; Chen, Danlei; Li, Xi; Wu, Renpei; Liu, Weifen; Leung, Joseph W.; Zhang, Chuansen; Li, Zhaoshen
Abstract : Abstract: There is no clinical report on the use of natural orifice transluminal endoscopic surgery (NOTES) for the management of patients with large liver cysts. This study aims to evaluate the feasibility and safety of NOTES for liver cyst fenestration in humans using a currently available technique. From February 2009 to June 2010, 4 cases of transgastric endoscopic liver cyst fenestration were performed; in which 3 cases received NOTES only, while 1 case received additional laparoscopic assistance. Mean time to endoscopically locate the liver cyst was 16 minutes (5–22 minutes). Cysts that were present in the left lobe or on the liver surface were easier to locate endoscopically. Transgastric endoscopic liver cyst fenestration was successful in all patients. The use of an occlusion balloon helped in the endoscopic clipping of the gastrotomy incision. Mean operative time was 101.3 minutes (range, 90–112 minutes), and there were no intra- or postoperative complications including infections. All patients recovered well after the surgery, with only minor postoperative throat pain. There was no recurrence at a mean follow-up of 12 months (range, 6–48 months). Small sample size. It may be technically feasible and safe to perform transgastric endoscopic liver cyst fenestration in humans with no recurrence at follow up. Abstract : Supplemental Digital Content is available in the text